Seasonal sexual activity of Nellore bulls and their cross-breed with Fleckvieh and Chianina: biometric testicular characteristics - Silva, Antônio Emidio Dias Feliciano; Dode, Margot Alves; Porto, João Abela; Abreu, Urbano Gomes P. (Pesquisa Agropecuaria Brasileira, 1991)
The effect of the seasonal changes (rainy, June October 1985; and dry, January May 1986) was studied on the biometric characteristics of ten bulls, six of Nellore breed and four crosses Fleckvieh and Chianina with Nelore. The breed influenced all the studied parameter. The body weight and scrotal circumference were higher in the crossbred bulls and the testicular consistency in the Nellore one. The body weight and scrotal circumference were higher in the rainy season and the testicular consistency in the dry season. The testicular consistency was negatively correlated (P < 0,01) with body weight, temperature and rain fall. The studied biometric characteristics of Nellore and crossbred bulls were influenced by seasonal variation. These results show better sexual activity during rainy season when there is more nutritional availability in Central Brazil.